'The object is to change the heart and soul': Financial incentives, planning and opposition to new housebuilding in England. (June 2020) - Inch, Andy; Dunning, Richard; While, Aidan; Hickman, Hannah; Payne, Sarah
In 2014 the UK government announced plans to reduce opposition to housing development by making a direct payment to households in England. 1 This was part of a wider experiment with behavioural economics and financial inducements in planning policy. In this paper, we explore this proposal, named 'Development Benefits', arguing it offers important insights into how the governing rationality of neoliberalism attempts to govern both planning and opposition to development by replacing political debate with a depoliticised economic rationality. Drawing on householder and key player responses to the Development Benefits proposal we highlight significant levels of principled objection to the replacement of traditional forms of planning reason with financial logics. The paper therefore contributes to understandings of planning as a site of ongoing resistance to neoliberal rationalities. We conclude by questioning whether Development Benefits represent a particular strand of 'late neoliberal' governmentality, exploring the potential for an alternative planning rationality to contest the narrow marketisation of planning ideas and practices.